Învățământul de administrație publică - Provocări și dileme - Sorin Dan ŞANDOR; Ciprian TRIPON; Raluca GÂRBOAN (Revista Transilvană de Ştiinţe Administrative, 2006)
The Romanian Higher Education System has suffered many changes during the last 15 years. The most recent one regards its reshaping from the point of view of the Bologna process. This article tries to assess the current state of Public Administration programs, stressing the following points: − The offering (in terms of curricula) of Romanian PA schools; − Possible academic success factors; − The students and their beliefs. The offer is very diverse (sometimes confusing), in which different schools of thought clash. For the student population it is impossible to find a link between academic success and highschool success. Some of the beliefs shared by many students may hinder learning, others do request modernizing teaching techniques. The massification of universities is bringing in this space many of the problems encountered in high schools and is impeding on the quality of studies.